Analisis Kebutuhan Internal dalam Diri Pekerja untuk Bekerja di Bawah Tekanan pada Bank Sumsel Babel Cabang Kertapati - Alghifari, M. Farhan; Almigo, Nuzsep (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Internal needs are intrinsic drives that motivate employees to work optimally, with varying motives such as income, a sense of security, or prestige. This community service activity was conducted through observation and interviews at Bank Sumsel Babel, Kertapati Branch Office. The results show that work pressure can motivate employees, depending on factors such as basic life needs, social environment, and the desire to improve professional competence. Pressure is not always negative; it can enhance motivation and performance, aligning with Maslow's hierarchy of needs, which emphasizes the gradual fulfillment of needs leading to self-actualization.